2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path712>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein in human gastrointestinal cancer

Abstract: Metallothionein (MT) is a small thiol-rich metalloprotein with antioxidant properties, involved in tumour pathophysiology and therapy resistance. In order to assess the contribution of MT in gastrointestinal carcinogenesis, this study examined both the MT content by radioimmunoassay and the MT localization by immunohistochemistry in pairs of neoplastic and normal-appearing human gastrointestinal tissues. In addition, the relationship between MT expression and major clinicopathological parameters was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 49 publications
5
45
0
5
Order By: Relevance
“…It has been observed that colorectal carcinogenesis is characterized by a significant decrease in MT expression (13). Conversely, in some conditions MT expression is consid-A B C D ered to be protective against cancer development or to indicate a better prognosis (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that colorectal carcinogenesis is characterized by a significant decrease in MT expression (13). Conversely, in some conditions MT expression is consid-A B C D ered to be protective against cancer development or to indicate a better prognosis (14).…”
Section: Resultsmentioning
confidence: 99%
“…This proposal is supported by the observation that MT is expressed in a patchy pattern in the neoplastic gastrointestinal tissues, with positive parts located next to negative parts (13), and that there is a clonal variation of the cadmium response in human tumor cell lines that may be related to the MT expression (21). Further studies are needed to confirm and further define the relationship between the spread of MTEC and its role in colonic carcinogenesis in rats treated with nimesulide or infected with T. cruzi.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh histologically normal tissue specimens of 79 patients (21 females and 58 males, mean age 66 years, range 35 -91 years) who underwent resection for primary gastric adenocarcinoma at the department of Oncologic Surgery of the Leiden University Medical Center were collected prospectively, as described before (Janssen et al, 2002). Various clinico-pathological data were (re-)evaluated or collected from patient files by one gastroenterologist and one pathologist (Janssen et al, 2002).…”
Section: Patients and Study Designmentioning
confidence: 99%
“…Various clinico-pathological data were (re-)evaluated or collected from patient files by one gastroenterologist and one pathologist (Janssen et al, 2002). All carcinomas were classified according to the TNM classification (Hermanek and Sobin, 1992) and localisation as well as diameters of the tumours were registered.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…We and others have previously demonstrated that these proteins are progressively silenced during colorectal cancer progression, and that this is associated to poorer patient survival. (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%